BLACK WOMEN IN LEADERSHIP: HOW TO GET THERE? - de Souza M. Mangianelli, Andrea; Luiz Barth, Wilmar (Revista Gênero e Interdisciplinaridade, 2022)
This study aims to identify the difficulties faced by black women who aim to occupy a leadership position within corporations, in addition to evaluating the process of black women who already occupy such a position. The evaluation will be carried out through research designed for such audiences and data collected by scholars on the subject.